Instructor – Cadets Interaction in Maritime English Classroom (A Case Study at Politeknik Pelayaran Barombong) - Fitriani Hilal (ELT Worldwide: Journal of English Language Teaching, 2022)
The present study was to explore instructor-cadets interaction in maritime English classrooms. Specifically, it sought to reveal (1) the patterns of the instructor-cadets interaction in the classrooms and (2) cadets’ perception on the indicated interaction patterns. Designed to be a single-case study, the research was conducted at Politeknik Pelayaran Barombong, Makassar, one of the leading seafaring education and training institutions in East-Indonesia. The data were obtained through classroom observation and interview.As the results, the findings elucidate that (1) the patterns of the instructor-cadets interaction were categorized into one-way, two-way, multi-way traffic, even there was a new hypothetical traffic proposition “semi multi-way traffic” identified emprically besides the three traffics, and (2) based on the cadets’ perceptions toward the indicated patterns, it could be revealed that (a) they were aware of the indicated patterns and (b) there are some determinant factors of the three indicated interacton patterns, especially for the one-way traffic, i.e; having not understood the lesson materials, fear of being underestimated, teacher’s negative prejudice behavior, and being exhausted physically and psychologically by the military learning activities.